2011
DOI: 10.1186/1743-422x-8-278
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus NSP4: Cell type-dependent transport kinetics to the exofacial plasma membrane and release from intact infected cells

Abstract: BackgroundRotavirus NSP4 localizes to multiple intracellular sites and is multifunctional, contributing to RV morphogenesis, replication and pathogenesis. One function of NSP4 is the induction of early secretory diarrhea by binding surface receptors to initiate signaling events. The aims of this study were to determine the transport kinetics of NSP4 to the exofacial plasma membrane (PM), the subsequent release from intact infected cells, and rebinding to naïve and/or neighboring cells in two cell types.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 88 publications
(125 reference statements)
1
22
0
Order By: Relevance
“…We reported apical secretion of NSP4 from rotavirus infected Caco-2 cells as an intact species without proteolytic cleavage [7]. Secretion of the unprocessed fully glycosylated form of NSP4 was surprising given the presence of a transmembrane domain but has been confirmed recently by Gibbons et al, [8]. The results presented here indicate that NSP4 is secreted as an oligomeric lipoprotein in complex with phospholipid.…”
Section: Discussionsupporting
confidence: 62%
“…We reported apical secretion of NSP4 from rotavirus infected Caco-2 cells as an intact species without proteolytic cleavage [7]. Secretion of the unprocessed fully glycosylated form of NSP4 was surprising given the presence of a transmembrane domain but has been confirmed recently by Gibbons et al, [8]. The results presented here indicate that NSP4 is secreted as an oligomeric lipoprotein in complex with phospholipid.…”
Section: Discussionsupporting
confidence: 62%
“…The ability of NSP4 to differentially interact with multiple viral and cellular proteins, including calnexin [68], laminin-3, fibronectin [69], caveolin [56], integrin I domains [**55], and tubulin [60] (Figure 3A) may be attributed to localization of NSP4 to different cellular compartments (ER [70], the ER-Golgi intermediate compartment (ERGIC), LC3-positive autophagosomes surrounding viroplasms [71], microtubules [60,63], membrane rafts [72,73], the exofacial surface of the plasma membrane [74], and the extracellular matrix [**55,69]) during different stages of infection and possibly to distinct forms or conformations of this multifunctional protein.…”
Section: Structural Studies Of Rotavirus Nspsmentioning
confidence: 99%
“…It is also known to interact with other rotaviral proteins (2,23,33,37) and cellular proteins, such as tubulin, caveolin, laminin-␤3, fibronectin, and integrin (7,38,43,45,50). Besides its association with several cellular compartments, it is also secreted in both cleaved (51) and native (10,20) forms from infected and NSP4 gene-transfected cells, which was proposed previously to bind to receptors on neighboring cells and induce diarrhea (43).…”
mentioning
confidence: 99%
“…During different stages of rotaviral infection, NSP4 has been proposed to be associated with diverse functions, such as the viroporin-associated alteration of Ca 2ϩ homeostasis by the release of Ca 2ϩ from the ER (16,24,47), the modification of membrane permeability (39), the triggering of an extracellular Ca 2ϩ signaling pathway (15,16), and interactions with and the transport of double-layered particles (DLPs) into the lumen of the ER for maturation into triple-layered particles (TLPs) (2,37). Although it was originally proposed to be an ER-anchored intracellular receptor for DLPs (2,5,11,37,46), several studies showed its presence in several other cellular sites, including the ER-Golgi intermediate compartment (ERGIC) (6,50), LC3-positive autophagosomes, and a novel membrane compartment colocalizing with viroplasms (6), membrane rafts (45), microtubules (50), the exofacial surface of the plasma membrane (20), and the extracellular matrix (7). While the N-terminal hydrophobic region anchors the protein to the ER or plasma membrane, the C-terminal part of the protein (residues 45 to 175) is oriented toward the cytoplasm or the extracellular environment (5,11,18,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation